Work on resolving Israeli-Palestinian conflict - Islam, Rafikul (Analytic Hierarchy Process(AHP) and Analytic Network Process(ANP), 2017)
Professor Thomas L. Saaty is a world-renowned Operations Research (OR) scientist. His death has created a vacuum which can hardly be filled up. His absence in scholastic writing in the field of MCDM will be widely felt for a long time. The world of OR will remember him not only as a mathematician, originator of AHP and ANP, but also as a good human being. He has numerous contributions in the field of OR, particularly MCDM. In the present article, I have highlighted his wonderful contribution in resolving the decade-long Israeli-Palestinian conflict.